Learners’ Views of Literature and Academic Achievement in a Literature Course: A Sample of ESL Pre-Service Teachers in Malaysia - Jamiah Baba (Asian TESOL Journal, 2022)
The advantages and disadvantages of literature in ESL contexts has been much discussed. Proponents argue that the drawbacks can be minimised if learners’ expectations, needs, and interests are carefully considered. This paper, therefore, attempts to describe learners’ views of literature and the challenges they face while learning literature and to understand whether these experiences have an impact on their academic achievement of a particular literature course. 35 pre-service teachers participated in the study by answering a questionnaire that comprises multiple-choice items and open-ended questions. The respondents were purposely selected as they are training to become English teachers, have taken at least eight literature courses, and are currently enrolled in at least one literature course. Frequency count was mainly used to describe the response to each item while crosstabulations are used whenever the responses are to be compared with each other. The learners’ academic grades were also analysed and cross tabulated with the items in the questionnaire. The findings show that the learners view literature positively and enjoyed learning literature, citing scaffolding and support as key factors. These findings have implications on how educators plan and teach literature courses, which can affect how ESL learners’ approach and learn literature.